PEMBELAJARAN DARING DI KELAS VB SD INPRES SERINGGU MERAUKE - Dewi Puji Rahayu; Karlina Wong Lieung; Ratna Purwanty (Institut Pendidikan Tapanuli Selatan, 2022)
This research intends to describe online learning in VB SD Inpres Seringgu Merauke. This research is a descriptive qualitative research. Data were collected using observation and interview techniques. This study found that online learning in VB SD Inpres Seringgu Merauke uses the whatsapp application. The teacher creates a whatsapp group, then the teacher adds students to the group. The implementation of learning through whatsapp is carried out by the teacher by sending learning materials and assignments that have been given by the teacher. Students are given the opportunity to ask questions by the teacher through personal chat. The teacher records students who have and have not submitted assignments. The teacher gives notes for students who have not submitted assignments via whatsapp groups and can be submitted directly to teachers at school.